PENGARUH PENGGUNAAN MEDIA GITAR TERHADAP PEMAHAMAN LAGU-LAGU NASIONAL DAN NILAI-NILAI NASIONAL SISWA KELAS V SD 6 JEKULO - Rosyada, Maftukhah; Wafiroh, Innarotul; Wafiroh, Wasis (Yayasan Amanah Nur Aman, 2025)
This study aims to determine the effectiveness of the use of guitar media in learning national songs for grade V elementary school students. The background of this research is the low participation of students and the lack of integration of character values in the learning of musical arts. The method used was quantitative with a pseudo-experimental design (one group pretest-posttest) with the subjects of 22 grade V students at SD 6 Jekulo. The research instruments include observations, pretest and posttest questions, and interviews. The results showed an increase in students' understanding of the national anthem after learning to use the guitar. The average pretest of 63.59 increased to 81.27 in the posttest with a significance of 0.000 (p < 0.05). Although only 36.4% of students actively play the guitar, singing participation and emotional involvement are quite high. Learning also instills national values contextually. Guitar media has proven to be effective as a fun and interactive means in improving learning outcomes and fostering students' national character. Follow-up research is recommended to be carried out with a longer duration and adequate supporting facilities.